Shopify application development : build highly effective Shopify apps using the powerful Ruby on Rails framework - Larkin, Michael (Community experience distilled., 2014)
This is an easy-to follow manual that will guide you through the entire process of application development with Shopify, beginning with the installation and configuration of your local development environment for your app to the deployment of the app to Heroku. If you are a web developer or a designer who wants to extend Shopify stores by building apps, then this book is for you. A basic understanding of programming concepts and some familiarity with Shopify is all that is required to get started with Shopify app development.